Our common journey : a transition toward sustainability (National Academy Press, 1999)
World human population is expected to reach upwards of 9 billion by 2050 and then level off over the next half-century. How can the transition to a stabilizing population also be a transition to sustainability? How can science and technology help to ensure that human needs are met while the planet's environment is nurtured and restored? Our Common Journey examines these momentous questions to draw strategic connections between scientific research, technological development, and societies' efforts to achieve environmentally sustainable improvements in human well being. The book argues that societies should approach sustainable development not as a destination but as an ongoing, adaptive learning process. Speaking to the next two generations, it proposes a strategy for using scientific and technical knowledge to better inform future action in the areas of fertility reduction, urban systems, agricultural production, energy and materials use, ecosystem restoration and biodiversity conservation, and suggests an approach for building a new research agenda for sustainability science. Our Common Journey documents large-scale historical currents of social and environmental change and reviews methods for "what if" analyses of possible future development pathways and their implications for sustainability. The book also identifies the greatest threats to sustainability--in areas such as human settlements, agriculture, industry, and energy--and explores the most promising opportunities for circumventing or mitigating these threats. It goes on to discuss what indicators of change, from children's birth-weights to atmosphere chemistry, will be most useful in monitoring a transition to sustainability. Presenting important details within a large vision, Our Common Journey will be of interest to policymakers, scientists, technology specialists, educators, and lay readers concerned about the prospects for global sustainable development